IoT Indoor Air Quality Monitoring System with Android App Integration - Gopal Krishnan, Shailiesh; Wan Kairuddin, Wan Nur Hafsha (Evolution in Electrical and Electronic Engineering, 2025)
Poor indoor air quality is a growing concern, especially in enclosed spaces in educational buildings such as classrooms and laboratories, due to its impact on human health, comfort, and productivity. This project presents an IoT-based indoor air quality monitoring system integrated with an Android mobile application. The system utilizes an ESP32 microcontroller connected to MQ-135, MQ-7, PM2.5, and DHT22 sensors to measure key air quality parameters, including carbon monoxide (CO), volatile organic compounds (VOCs), particulate matter (PM2.5), temperature, and humidity. Data is transmitted in real-time to the ThingSpeak platform, which then displays on the custom-built Android App. An extractor fan is also integrated to automatically turn ON when the pollutant exceeds the defined threshold value. This system was tested at multiple laboratories and classrooms for its efficiency. Based on the test, the system has successfully detected pollutant levels and also activated the extractor fan at high pollution readings.